2017
DOI: 10.1097/md.0000000000008317
|View full text |Cite
|
Sign up to set email alerts
|

The thorax trauma severity score and the trauma and injury severity score

Abstract: Several scoring systems are commonly used to evaluate severity in patients with traumatic injuries. However, there is no generally accepted standard scoring system to assess the severity of thoracic trauma, specifically in patients who have sustained severe injuries. The present study aimed to evaluate the validity of the trauma and injury severity score (TRISS) and the thorax trauma severity score (TTSS) as predictors of in-hospital mortality in patients with severe thoracic trauma.We conducted a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…Calculating the TRISS, eighty-seven of the patients had a probability of survival above 90%, similar to the results of Carrapateira et al, who found that 85,2% of the patients studied had a probability of survival between 98 and 99% [27] . In the Intensive Care Unit in Gyeongsang, Korea, Moon et al evaluated 228 patients and obtained a lower probability of survival than our study, a median of 49,4%, ranging from 24,5 to 75,5%, but only included severe patients with ISS > 18 [29] .…”
Section: Discussioncontrasting
confidence: 63%
“…Calculating the TRISS, eighty-seven of the patients had a probability of survival above 90%, similar to the results of Carrapateira et al, who found that 85,2% of the patients studied had a probability of survival between 98 and 99% [27] . In the Intensive Care Unit in Gyeongsang, Korea, Moon et al evaluated 228 patients and obtained a lower probability of survival than our study, a median of 49,4%, ranging from 24,5 to 75,5%, but only included severe patients with ISS > 18 [29] .…”
Section: Discussioncontrasting
confidence: 63%
“…Related studies have discovered major associated injuries and worse categories of injury severity scores as some of the determinants of mortality in chest injury. 2,10,13,18 Management followed the set protocols with additional infection prevention control guidelines re-amplified during the COVID-19 era. Pre-administration of the checklist for COVID-19 triage often resulted in suspiciously high score in many of our patients who presented with low values of peripheral arterial oxygen saturation (SpO2).…”
Section: Discussionmentioning
confidence: 99%
“…Although useful, the TTSS is limited in that it was designed for use in patients of advanced age, and follow-up studies have challenged its ability to predict mortality. 22 Arguably, the most widely used scoring system in recent literature is the RibScore, described by Chapman et al 11 Chapman incorporated specific anatomical factors in the RibScore to effectively predict adverse pulmonary outcomes. Although revolutionary in its ability to standardize the assessment of fracture severity and prognostication for trauma patients, this scoring system only evaluates patients at the time of admission and relies solely on radiographic findings with no evaluation of patient physiology.…”
Section: Discussionmentioning
confidence: 99%
“…The TTSS was among the first scoring systems developed that did not solely focus on the number of rib fractures present. Although useful, the TTSS is limited in that it was designed for use in patients of advanced age, and follow-up studies have challenged its ability to predict mortality 22 . Arguably, the most widely used scoring system in recent literature is the RibScore, described by Chapman et al 11 Chapman incorporated specific anatomical factors in the RibScore to effectively predict adverse pulmonary outcomes.…”
Section: Discussionmentioning
confidence: 99%